Influence of site factors on offshore ground motions: Observed Results and Numerical Simulation. Issue 145 (June 2021) - Chen, Baokui; Wang, Dongsheng; Chen, Shaolin; Hu, Sicong
Abstract: More offshore structures such as sea-crossing bridges, undersea tunnels, and subsea pipelines are being constructed than ever. Owing to the lack of offshore strong motion records, onshore ground motions are used to assess the seismic behaviors of offshore structures, but onshore and offshore ground motions are significantly different from each other. In this study, the statistical characteristics of offshore strong motion records are investigated. Site factors are found to affect offshore ground motion. A comprehensive numerical analysis is then conducted to understand the influence of sloped terrain and silt soft-soil layer on offshore ground motions. The results indicate that a silt soft-soil layer on the seabed has a considerable amplification effect on the horizontal component of SV-wave. Moreover, the sloped terrain on the seabed can substantially enlarge the vertical component of P-wave. Highlights: The statistical characteristics of offshore strong motion records are investigated. A novel model is built to simulate the propagation process of offshore ground motions. The influence of the sloped terrain on offshore ground motions is studied. The influence of the silt layer on offshore motions is analyzed by numerical method.